Selectivity and fish catches of gillnets in stratum VII (Yeji sector) of Lake Volta for sustainable management - Daniel N. Akongyuure; Patrick K. Ofori-Danson; Francis K. E. Nunoo (Advances in Aquaculture and Fisheries Management, 2020)
The study was conducted in Stratum VII (Yeji sector) of Lake Volta where commercial fishermen arbitrarily use gillnets, from June, 2009 to March, 2010. The catches of monofilament gillnets, the most dominant gear used in Stratum VII were investigated for dominant fish species composition and selectivity parameters. The study revealed the dominance of two fish species (Synodontis membranaceus and Schilbe mystus) which together contributed about 45% by number of gillnet catches. The optimum selection length (total length) of the 5 cm mesh size gillnet for S. membranaceus was 19.7 cm and S. mystus was 18.2 cm. The result showed that using monofilament gillnets with mesh sizes 3 and 5 cm could have increase pressure on juvenile population. The mean monthly catch for the study period was estimated to be in the range of 0.3961 × 10-3 – 3.2427 × 10-3 (standard deviation, δ=1003.9) metric tonnes. With reference to precautionary approach to fisheries management, a legal minimum mesh size of gillnets of 8 cm may be appropriate for conservation and sustainable exploitation in Stratum VII